An Order of Priorities in Confronting Iran. Issue 2 (4th March 2017) - Fitzpatrick, Mark
Abstract : It is far better to implement an incomplete but effective nuclear agreement than to scrap it, hoping to achieve the best outcome while ending up with the worst.